Critical Thinking Skills Using Science Technology Religion Engineering Arts and Mathematics (STREAM) Approach on Ecosystem Materials - Muhammad Hasymi Mujaddi; Tri Wahyu Agustina; Sri Maryanti (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2022)
One of the habits of mind developed in the 21st century is critical thinking skills. This study aims to describe the increase in students' critical thinking skills after learning using the approach of science, technology, religion, engineering, art, and mathematics (STREAM) on ecosystem materials. This research was conducted in one of the public high schools in Bandung Regency with a pre-experiment method whit one group pretest posttest design. The research sample was 35 students who were selected through purposive sampling technique. The instrument used is in the form of test questions that refer to the indicators of critical thinking skills as follows: giving simple explanations, building basic skills, concluding, providing further explanations and developing strategies and tactics. The data analysis technique used is to perform statistical tests. Based on the results of the study, the average value of the N-Gain critical thinking skills of students in classes using the STREAM approach was 67% in the medium category. The highest increase is in the indicator of setting strategy and tactics by 67% in the medium category. The lowest increase is the indicator providing a simple explanation of 49% in the medium category. The results of the study indicate that the STREAM approach can improve students' critical thinking skills